Evaluating the shifting priorities of Uganda’s agricultural extension services: A micro perspective - Van Campenhout, Bjorn; Nattembo, Fiona; Pauw, Karl (International Food Policy Research Institute, 2018)
The Ugandan government is increasingly emphasizing input distribution over extension advisory services in its agricultural budget allocations, broadly defined. Both expenditure items are arguably important; hence, this note makes an empirical case for a more balanced approach to allocating public resources within the agricultural sector. Econometric results from official household-level survey data suggest that combining inputs and extension services is associated with higher yields. For maize and groundnut, in particular, the benefits of offering modern inputs and extension together exceed those of providing either exclusively. We conclude that the government’s current approach, which focuses mainly on the logistics of input distribution, may be misguided.